(untitled) (Revista Brasileira Multidisciplinar, 2019)
This work aims to contribute to the development of improvements in the logistics adopted for the selective collection of recyclable material, as well as in the development of environmental education work. For this purpose, a pilot project of selective collection is proposed, using a Voluntary Delivery Point (VDP) to replace door-to-door collection logistics, together with an intensive education campaign for the use of the VDP. In its first phase of the project, carried out on two streets in the Campos Elíseos neighborhood of Poços de Caldas-MG, the viability of the implementation of the VDP was verified from the data obtained by performing an analysis before and after the implementation of the VDP. The results show a reduction of 70% in the collection time, a 40.4% fall in the distance traveled by the collectors, as well as the diesel economy.